Penggunaan Darah Kadarluarsa Sebagai Media Isolasi dan Identifikasi Streptococcus faecalis - Mudatsir Mudatsir (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2010)
Efforts to find microbes in microbiological examination of material are carried out by means of isolation and identification of microorganisms from the examination material. Isolation was carried out using culture medium. Use a medium for the isolation and identification are closely related with one of Koch's postulates, that is causing the infection must be cultured in the laboratory. Research on the use of expired blood as a medium of isolation and identification of Streptococcus pyogenes has been performed. The aim study is to determine the viability of the colony and the size of the zone of hemolysis of Streptococcus pyogenes in the blood as a medium expired. Materials use is expired blood 1, 2, 3 and 4 weeks. Isolation procedures and identification of Streptococcus pyogenes include Gram stain, type of hemolysis, catalase test, and test basitrasin. The results showed the blood expired before four weeks show the number of colonies was almost the same viability with sheep blood agar medium and large blood hemolysis zone are also nearly equal to expire so that the blood of sheep prior to 4 weeks. Thus the blood is exceeded before the 4 weeks can be used as media for the isolation and identification of Streptococcus pyogenes